Resource utilization method of clay lithium slag and cat litter prepared from clay lithium slag
By mixing clay lithium slag with calcium salt and aged and acidifying, it is converted into bentonite for preparation of cat litter, the land waste and environmental pollution caused by lithium slag accumulation are solved, and the efficient and low-energy resource utilization of lithium slag is achieved.
Patent Information
- Application Number
- CN202411831966.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-25
AI Technical Summary
The accumulation of lithium slag leads to land waste and environmental pollution. The existing lithium slag utilization process has problems such as high energy consumption, low added value and low utilization methods.
By mixing clay lithium slag with calcium salt, aged, acidizing, and converting it into bentonite to prepare cat litter, thereby achieving high-value utilization of lithium slag.
The low-energy consumption and high added value of lithium slag are achieved, and the cat litter produced has excellent water absorption and cohesion.
Smart Images

Figure CN119866954A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resource utilization of solid waste, and in particular to a resource utilization method of clay lithium slag and cat litter prepared therefrom. Background Art
[0002] With the strong rise of new energy storage industries represented by lithium batteries, lithium salt industries such as lithium carbonate, lithium hydroxide, and lithium chloride have achieved great development, but the corresponding industrial waste lithium slag production has increased year by year. Usually, 8 to 10 tons of lithium slag will be produced for every ton of lithium salt produced. In 2018, the total domestic production of lithium carbonate was 125,000 tons. According to calculations, the annual discharge of lithium slag will reach about 1.25 million tons. Combined with the accumulated accumulation over the years, the domestic lithium slag stockpile can reach tens of millions of tons. The accumulation of lithium slag will cause a lot of land waste and environmental pollution.
[0003] At present, the relevant research on lithium slag is mainly focused on the comprehensive utilization of lithium slag, and mainly tends to be related fields such as building materials manufacturing. However, due to the uneven process levels, the utilization of lithium slag is not high and the utilization method is relatively low-end and low-value. For example, lithium slag is used to make lightweight ceramic plates, including taking lithium slag, feldspar, quartz powder, alumina and other raw materials for dry powdering, mixing them in proportion to obtain a mixture; adding water to the mixture, stirring, granulating, drying, and sieving to obtain granular materials; loading the granular materials into a sagger, flattening them, and then high-temperature firing, and cooling them to obtain lightweight ceramic plates. This method has the following shortcomings: (1) It is required that the lithium slag used contains more than 5.5% manganese monoxide, and the content of lithium slag is required to be relatively high; (2) The high-temperature firing temperature is above 1000°C, the production energy consumption is very high, and the industrial production cost is high. In addition, lithium slag from lithium mica smelting is mixed and stirred with an aqueous solution, and multi-stage stirring, washing and filter pressing are performed at 40 to 60°C to obtain a filter cake and a filtrate. After impurity removal, the high-salt purified liquid is treated by vacuum pervaporation and thermal pervaporation to precipitate potassium sulfate and sodium sulfate, respectively, to obtain industrial-grade sodium sulfate and potassium sulfate products. This method has the following shortcomings: (1) multi-stage stirring, washing, filtration and multiple impurity removal are used, the process is complex and the operation is cumbersome; (2) only sulfate in the lithium slag is recycled, and a large amount of filter residue is still produced during the recycling process, and the problem of waste residue disposal cannot be solved. There is also a method for preparing ultra-light ceramsite by jointly absorbing lithium slag and fly ash. The method mainly includes: mixing and granulating lithium slag, fly ash, and feldspar in proportion, and then obtaining an ultra-light ceramsite product after two roasting treatments. This method has the following disadvantages: (1) two roasting processes are used, with the temperatures being above 450°C and above 1150°C respectively, resulting in high roasting energy consumption and high production costs; and (2) the prepared product has low market value and low economic benefits.
[0004] Therefore, there is an urgent need to provide a lithium slag treatment method to solve the above problems. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a resource utilization method of clay lithium slag and cat litter prepared therefrom, which has the advantages of low energy consumption, high added value of lithium slag and full utilization.
[0006] To this end, the first aspect of the present invention provides a method for resource utilization of clay lithium slag, comprising:
[0007] Mixing clay lithium slag and calcium salt to obtain a mixture 1;
[0008] The mixture 1 and the hydroxide are mixed and aged to obtain a mixture 2;
[0009] The mixture 2 is subjected to an acidification treatment to obtain a mixture 3, and the mixture 3 is used to prepare cat litter.
[0010] In view of the problem that the existing slag from lithium extraction from clay by sulfate process cannot be utilized, the present invention converts muscovite and illite in the lithium slag into bentonite by aging with calcium salt and hydroxide, and then acidifies to obtain a mixture 3, the main component of which is bentonite, which can be used as cat litter, thereby realizing the high-value utilization of the clay lithium slag. Therefore, the solution provided by the present invention provides a direction for the waste slag treatment problem of lithium extraction from clay by sulfate process, and has the advantages of low energy consumption, high added value of lithium slag and full utilization.
[0011] According to an embodiment of the present invention, the calcium salt includes at least one of calcium carbonate, calcium sulfate, calcium chloride and calcium nitrate.
[0012] According to an embodiment of the present invention, the mass ratio of the clay lithium slag to the calcium salt is 1:(0.2-1).
[0013] According to an embodiment of the present invention, the hydroxide includes at least one of sodium hydroxide and potassium hydroxide.
[0014] According to an embodiment of the present invention, the mass ratio of the mixture 1 to the hydroxide is 1:(0.3-0.6).
[0015] According to an embodiment of the present invention, the temperature of the aging treatment is 50°C-80°C.
[0016] According to an embodiment of the present invention, the aging treatment time is 15d-45d.
[0017] According to an embodiment of the present invention, the acidification treatment includes contacting the mixture 2 with an acidic compound to obtain the mixture 3.
[0018] According to an embodiment of the present invention, the acidic compound includes at least one of sulfuric acid and hydrochloric acid.
[0019] According to an embodiment of the present invention, the acidification treatment time is 30 min-90 min.
[0020] According to an embodiment of the present invention, the mass ratio of the clay lithium slag to the acidic compound is 1:(0.8-2).
[0021] According to an embodiment of the present invention, the method further comprises: mixing the mixture 3 with a deodorant, an antibacterial agent, and a binder, and granulating the mixture to obtain a mixture 4, wherein the mixture 4 is used as cat litter.
[0022] According to an embodiment of the present invention, the deodorant includes at least one of modified zeolite, bamboo charcoal powder, and coconut shell activated carbon.
[0023] According to an embodiment of the present invention, the antibacterial agent includes at least one of a pyridine aqueous dispersant and a polyguanidine aqueous solution.
[0024] According to an embodiment of the present invention, the binder includes water glass.
[0025] According to an embodiment of the present invention, the mass ratio of the clay lithium slag to the deodorant is 1:(0.03-0.15).
[0026] According to an embodiment of the present invention, the mass ratio of the clay lithium slag to the antibacterial agent is 1:(0.03-0.06).
[0027] According to an embodiment of the present invention, the mass ratio of the clay lithium slag to the binder is 1:(0.30-0.45).
[0028] According to an embodiment of the present invention, the particle size of the mixture 4 is 3 mm-6 mm.
[0029] According to an embodiment of the present invention, the length of the mixture 4 is 6 mm-8 mm.
[0030] According to an embodiment of the present invention, the method further includes: drying the mixture 3 for preparing cat litter, or drying the mixture 4 for use as cat litter.
[0031] According to an embodiment of the present invention, the drying temperature is 70°C-90°C.
[0032] According to an embodiment of the present invention, the particle size of the clay lithium slag is 80-200 mesh.
[0033] The second aspect of the present invention provides a cat litter, which is obtained according to the resource utilization method of the first aspect. The cat litter has excellent water absorption and clumping properties.
[0034] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0036] Figure 1 The flowchart of the resource utilization method of clay lithium slag provided by the present invention is shown. DETAILED DESCRIPTION
[0037] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0038] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0039] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0040] In order to make the present invention more easily understood, certain technical and scientific terms are specifically defined below. Unless otherwise clearly defined elsewhere in this document, all other technical and scientific terms used herein have the meanings commonly understood by those skilled in the art to which the present invention belongs.
[0041] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0042] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0043] According to an embodiment of the present invention, a first aspect of the present invention provides a method for resource utilization of clay lithium slag, and the resource utilization method of clay lithium slag comprises:
[0044] (1) Mixing clay lithium slag and calcium salt to obtain a mixture 1.
[0045] According to a specific embodiment of the present invention, the type of calcium salt is not particularly limited, and it can provide calcium ions to convert clay lithium slag into calcium-based bentonite. As some specific examples, they include but are not limited to calcium carbonate, calcium sulfate, calcium chloride, calcium nitrate, etc., preferably calcium carbonate and / or calcium sulfate.
[0046] According to a specific embodiment of the present invention, the mass ratio of the clay lithium slag to the calcium salt is 1:(0.2-1), for example, 1:0.2, 1:0.4, 1:0.6, 1:0.8, 1:1, etc.
[0047] According to a specific embodiment of the present invention, the particle size of the clay lithium slag is 80-200 mesh, which can be achieved by crushing and the like.
[0048] (2) Mixing the mixture 1 and the hydroxide, and performing an aging treatment to obtain a mixture 2.
[0049] In this way, muscovite and illite in the clay lithium slag can be converted into bentonite. Bentonite is a clay mainly composed of montmorillonite minerals. Each bentonite particle is composed of thousands of tiny montmorillonite crystal nanosheets. Montmorillonite crystals are composed of two layers of silicon-oxygen tetrahedrons with a layer of aluminum-oxygen octahedron in the middle. A large number of exchangeable cations are adsorbed between the crystal layers. The exchangeable cations between the crystal layers become hydrated cations after encountering water, which greatly increases the distance between the montmorillonite crystal nanosheets. As a result, the gaps between the nanosheets, the structural units of montmorillonite, can accommodate a large number of water molecules. Therefore, bentonite has excellent water absorption and can be used as a cat litter product in the future to achieve high-value utilization of clay lithium slag.
[0050] According to a specific embodiment of the present invention, the type of hydroxide is not particularly limited, and some specific examples include but are not limited to sodium hydroxide, potassium hydroxide, etc. The hydroxide is preferably sodium hydroxide.
[0051] According to a specific embodiment of the present invention, the mass ratio of the mixture 1 to the hydroxide is 1:(0.3-0.6), for example, 1:0.3, 1:0.4, 1:0.5, 1:0.6, etc.
[0052] According to a specific embodiment of the present invention, the mixture 1 and the hydroxide solution are mixed and aged to obtain a mixture 2. The mass ratio of the mixture 1 to the hydroxide solution is 1:(0.3-0.6), such as 1:0.3, 1:0.4, 1:0.5, 1:0.6, etc. The concentration of the hydroxide solution can be 5%-15%, and those skilled in the art can select it according to the situation, for example, the concentration of the hydroxide solution is 5%, 10%, 15%, etc.
[0053] According to a specific embodiment of the present invention, the temperature and time of the aging treatment are not particularly limited, and those skilled in the art may select them according to the circumstances. As some specific examples, the temperature of the aging treatment is 50°C-80°C, such as 50°C, 60°C, 70°C, 80°C, etc. The time of the aging treatment is 15d-45d, such as 15d, 20d, 25d, 30d, 35d, 40d, 45d, etc.
[0054] (3) The mixture 2 is subjected to an acidification treatment to obtain a mixture 3, and the mixture 3 is used to prepare cat litter.
[0055] According to a specific embodiment of the present invention, the acidification treatment includes contacting the mixture 2 with an acidic compound, and obtaining the mixture 3 through an acid-base neutralization reaction. The type of the acidic compound is not particularly limited, and includes but is not limited to sulfuric acid, hydrochloric acid, etc. Further, the acidic compound participates in the reaction in the form of a solution, and the concentrations of the sulfuric acid solution and the hydrochloric acid solution are not particularly limited. The concentration of the sulfuric acid solution may be 3%-10%, such as 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., and the concentration of the hydrochloric acid solution may be 3%-15%, such as 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc.
[0056] According to a specific embodiment of the present invention, the acidification treatment time is 30 min-90 min, such as 30 min, 60 min, 90 min, etc. The treatment is preferably carried out by stirring, and the rotation speed can be selected according to the situation, such as 100 r / min-300 r / min.
[0057] According to a specific embodiment of the present invention, the mass ratio of the clay lithium slag to the acidic compound is 1:(0.8-2), for example, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, etc.
[0058] According to a specific embodiment of the present invention, the mass ratio of the clay lithium slag to the acidic compound solution is 1:(0.8-2), for example, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, etc.
[0059] According to a specific embodiment of the present invention, after the acidification treatment, the sample can be filtered, dried, and then crushed to a size of 80 mesh or more, such as 80 mesh to 200 mesh.
[0060] According to a specific embodiment of the present invention, the method further comprises: mixing the mixture 3 with a deodorant, an antibacterial agent, and a binder, and granulating to obtain a mixture 4, wherein the mixture 4 is used as cat litter. For a specific process, see Figure 1 . This further improves the material's properties.
[0061] According to a specific embodiment of the present invention, the types of the deodorant, antibacterial agent, and binder are not particularly limited, and the deodorant includes but is not limited to bamboo charcoal powder, modified zeolite, and coconut shell activated carbon, which can not only play a deodorizing effect but also enhance the water absorption and cohesion of the mixture 4. The antibacterial agent includes but is not limited to pyridine water dispersants and polyguanidine aqueous solutions, and the binder includes but is not limited to water glass.
[0062] According to a specific embodiment of the present invention, the mass ratio of the clay lithium slag to the deodorant is 1:(0.03-0.15), for example, 1:0.03, 1:0.04, 1:0.05, 1:0.07, 1:0.09, 1:0.10, 1:0.11, 1:0.12, 1:0.13, 1:0.14, 1:0.15, etc. The mass ratio of the clay lithium slag to the antibacterial agent is 1:(0.03-0.06), for example, 1:0.03, 1:0.04, 1:0.05, 1:0.06, etc.
[0063] According to a specific embodiment of the present invention, the mass of the binder is not particularly limited. As some specific examples, the mass ratio of the clay lithium slag to the binder can be 1:(0.30-0.45), for example, 1:0.3, 1:0.32, 1:0.34, 1:0.36, 1:0.38, 1:0.39, 1:0.41, 1:0.42, 1:0.44, and 1:0.45.
[0064] According to a specific embodiment of the present invention, the particle size of the mixture 4 is 3 mm-6 mm, such as 3 mm, 4 mm, 5 mm, 6 mm, etc. The length of the mixture 4 is 6 mm-8 mm, such as 6 mm, 7 mm, 8 mm, etc. Among them, cat litter is mostly cylindrical in shape, so the length of the mixture 4 refers to the height of the cylinder.
[0065] According to a specific embodiment of the present invention, the method further comprises: drying the mixture 3 for preparing cat litter, or drying the mixture 4 for use as cat litter. The drying temperature is not particularly limited, and as some specific examples, it can be carried out at 70°C-90°C, and after drying, the mixture is sieved to remove particles and dust whose particle sizes do not meet the standards, so as to obtain the mixture 3 that can be used to prepare cat litter, or the mixture 4 that can be used as cat litter.
[0066] According to an embodiment of the present invention, a second aspect of the present invention provides a cat litter, which is obtained according to the resource utilization method described in the first aspect. Thus, the cat litter has good water absorption and clumping properties.
[0067] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0068] Example 1
[0069] 1. Crush the clay lithium slag, and pass it through a 100-mesh sieve to obtain a lithium slag raw material;
[0070] 2. Weigh 500 g of lithium slag raw material, add 200 g of calcium carbonate, and mix thoroughly to obtain a mixture 1;
[0071] 3. Place mixture 1 in a culture dish, slowly add 300 g of 10% sodium hydroxide solution to mixture 1, stir continuously during the process, seal with plastic wrap after stirring evenly, place in a 60° C. oven for aging for 40 days, and obtain mixture 2;
[0072] 4. Add 400 g of 5% sulfuric acid solution to mixture 2, stir for 60 min at a stirrer speed of 200 r / min for acidification, and obtain mixture 3;
[0073] 5. After acidification, filter and dry. After drying, crush the sample and pass it through a 100-mesh sieve. Add 20 g of modified zeolite passed through an 80-mesh sieve and 50 g of bamboo charcoal powder and mix evenly.
[0074] 6. Add 25 g of 75% fluazifop-thiamethoxam water dispersant and 195 g of water glass to the mixture obtained in step 5 and mix and granulate the mixture to a particle size of 4 mm and a length of 7 mm;
[0075] 7. After granulation, place the pellets in an oven at 80°C for drying. After drying, sieve the pellets to remove particles and dust that do not meet the standards, thereby obtaining bentonite cat litter.
[0076] Example 2
[0077] 1. Crush the clay lithium slag, and pass it through a 100-mesh sieve to obtain a lithium slag raw material;
[0078] 2. Weigh 500 g of lithium slag raw material, add 200 g of calcium sulfate, and mix thoroughly to obtain a mixture 1;
[0079] 3. Place mixture 1 in a culture dish, slowly add 300 g of 10% sodium hydroxide solution to mixture 1, stir continuously during the process, seal with plastic wrap after stirring evenly, place in a 60° C. oven for aging for 40 days, and obtain mixture 2;
[0080] 4. Add 400 g of 5% sulfuric acid solution to mixture 2, stir for 60 min at a stirrer speed of 200 r / min for acidification, and obtain mixture 3;
[0081] 5. After acidification, filter and dry. After drying, crush the sample and pass it through a 100-mesh sieve. Add 20 g of modified zeolite passed through an 80-mesh sieve and 50 g of bamboo charcoal powder and mix evenly.
[0082] 6. Add 25 g of 75% fluazifop-thiamethoxam water dispersant and 195 g of water glass to the mixture obtained in step 5 and mix and granulate the mixture to a particle size of 4 mm and a length of 7 mm;
[0083] 7. After granulation, place the pellets in an oven at 80°C for drying. After drying, sieve the pellets to remove particles and dust that do not meet the standards, thereby obtaining bentonite cat litter.
[0084] Example 3
[0085] 1. Crush the clay lithium slag, and pass it through a 100-mesh sieve to obtain a lithium slag raw material;
[0086] 2. Weigh 500 g of lithium slag raw material, add 100 g of calcium carbonate and 100 g of calcium sulfate, and mix thoroughly to obtain a mixture 1;
[0087] 3. Place mixture 1 in a culture dish, slowly add 300 g of 10% sodium hydroxide solution into mixture 1, stir continuously during the process, seal with plastic wrap after stirring evenly, place in a 60° C. oven for aging for 30 days, and obtain mixture 2;
[0088] 4. Add 200 g of 5% sulfuric acid solution and 200 g of 10% hydrochloric acid solution to mixture 2, and stir at a stirrer speed of 200 r / min for 60 min for acidification to obtain mixture 3;
[0089] 5. After acidification, filter and dry. After drying, crush the sample and pass it through a 100-mesh sieve. Add 20 g of modified zeolite passed through an 80-mesh sieve and 50 g of bamboo charcoal powder and mix evenly.
[0090] 6. Add 25 g of 75% fluazifop-thiamethoxam water dispersant and 195 g of water glass to the mixture obtained in step 5 and mix and granulate the mixture to a particle size of 4 mm and a length of 7 mm;
[0091] 7. After granulation, place the pellets in an oven at 80°C for drying. After drying, sieve the pellets to remove particles and dust that do not meet the standards, thereby obtaining bentonite cat litter.
[0092] Example 4
[0093] 1. Crush the clay lithium slag, and pass it through a 100-mesh sieve to obtain a lithium slag raw material;
[0094] 2. Weigh 500 g of lithium slag raw material, add 150 g of calcium carbonate and 150 g of calcium sulfate, and mix thoroughly to obtain a mixture 1;
[0095] 3. Place mixture 1 in a culture dish, slowly add 300 g of 10% sodium hydroxide solution into mixture 1, stir continuously during the process, seal with plastic wrap after stirring evenly, place in a 60° C. oven for aging for 30 days, and obtain mixture 2;
[0096] 4. Add 200 g of 5% sulfuric acid solution and 200 g of 10% hydrochloric acid solution to mixture 2, and stir at a stirrer speed of 200 r / min for 60 min for acidification to obtain mixture 3;
[0097] 5. After acidification, filter and dry. After drying, crush the sample and pass it through a 100-mesh sieve. Add 20 g of modified zeolite passed through an 80-mesh sieve and 50 g of bamboo charcoal powder and mix evenly.
[0098] 6. Add 25 g of 75% fluazifop-thiamethoxam water dispersant and 220 g of water glass to the mixture obtained in step 5 and mix and granulate the mixture to a particle size of 4 mm and a length of 7 mm;
[0099] 7. After granulation, place the pellets in an oven at 80°C for drying. After drying, sieve the pellets to remove particles and dust that do not meet the standards, thereby obtaining bentonite cat litter.
[0100] Example 5
[0101] 1. Crush the clay lithium slag, and pass it through a 100-mesh sieve to obtain a lithium slag raw material;
[0102] 2. Weigh 500 g of lithium slag raw material, add 150 g of calcium carbonate and 100 g of calcium sulfate, and mix thoroughly to obtain a mixture 1;
[0103] 3. Place mixture 1 in a culture dish, slowly add 350 g of 10% sodium hydroxide solution to mixture 1, stir continuously during the process, seal with plastic wrap after stirring evenly, place in a 60° C. oven for aging for 30 days, and obtain mixture 2;
[0104] 4. Add 300 g of 5% sulfuric acid solution and 200 g of 10% hydrochloric acid solution to mixture 2, stir at a stirrer speed of 200 r / min for 60 min for acidification, and obtain mixture 3;
[0105] 5. After acidification, filter and dry. After drying, crush the sample and pass it through a 100-mesh sieve. Add 20 g of modified zeolite passed through an 80-mesh sieve and 50 g of bamboo charcoal powder and mix evenly.
[0106] 6. Add 25 g of 75% fluazifop-thiamethoxam water dispersant and 205 g of water glass to the mixture obtained in step 5 and mix and granulate the mixture to a particle size of 4 mm and a length of 7 mm;
[0107] 7. After granulation, place the pellets in an oven at 80°C for drying. After drying, sieve the pellets to remove particles and dust that do not meet the standards, thereby obtaining bentonite cat litter.
[0108] Example 6
[0109] 1. Crush the clay lithium slag, and pass it through a 100-mesh sieve to obtain a lithium slag raw material;
[0110] 2. Weigh 500 g of lithium slag raw material, add 150 g of calcium carbonate and 100 g of calcium sulfate, and mix thoroughly to obtain a mixture 1;
[0111] 3. Place mixture 1 in a culture dish, slowly add 350 g of 8% sodium hydroxide solution into mixture 1, stir continuously during the process, seal with plastic wrap after stirring evenly, place in a 60° C. oven for aging for 40 days, and obtain mixture 2;
[0112] 4. Add 200 g of 5% sulfuric acid solution and 200 g of 10% hydrochloric acid solution to mixture 2, and stir at a stirrer speed of 200 r / min for 60 min for acidification to obtain mixture 3;
[0113] 5. After acidification, filter and dry. After drying, crush the sample and pass it through a 100-mesh sieve. Add 20 g of modified zeolite passed through an 80-mesh sieve and 50 g of bamboo charcoal powder and mix evenly.
[0114] 6. Add 25 g of 75% fluazifop-thiamethoxam water dispersant and 205 g of water glass to the mixture obtained in step 5 and mix and granulate the mixture to a particle size of 4 mm and a length of 7 mm;
[0115] 7. After granulation, place the pellets in an oven at 80°C for drying. After drying, sieve the pellets to remove particles and dust that do not meet the standards, thereby obtaining bentonite cat litter.
[0116] Example 7
[0117] 1. Crush the clay lithium slag, and pass it through a 100-mesh sieve to obtain a lithium slag raw material;
[0118] 2. Weigh 500 g of lithium slag raw material, add 150 g of calcium carbonate and 100 g of calcium sulfate, and mix thoroughly to obtain a mixture 1;
[0119] 3. Place mixture 1 in a culture dish, slowly add 350 g of 15% sodium hydroxide solution to mixture 1, stir continuously during the process, seal with plastic wrap after stirring evenly, place in a 60° C. oven for aging for 25 days, and obtain mixture 2;
[0120] 4. Add 300 g of 5% sulfuric acid solution and 200 g of 10% hydrochloric acid solution to mixture 2, stir at a stirrer speed of 200 r / min for 60 min for acidification, and obtain mixture 3;
[0121] 5. After acidification, filter and dry. After drying, crush the sample and pass it through a 100-mesh sieve. Add 20 g of modified zeolite passed through an 80-mesh sieve and 50 g of bamboo charcoal powder and mix evenly.
[0122] 6. Add 25 g of 75% fluazifop-thiamethoxam water dispersant and 205 g of water glass to the mixture obtained in step 5 and mix and granulate the mixture to a particle size of 4 mm and a length of 7 mm;
[0123] 7. After granulation, place the pellets in an oven at 80°C for drying. After drying, sieve the pellets to remove particles and dust that do not meet the standards, thereby obtaining bentonite cat litter.
[0124] Example 8
[0125] 1. Crush the clay lithium slag, and pass it through a 100-mesh sieve to obtain a lithium slag raw material;
[0126] 2. Weigh 500 g of lithium slag raw material, add 150 g of calcium carbonate and 100 g of calcium sulfate, and mix thoroughly to obtain a mixture 1;
[0127] 3. Place mixture 1 in a culture dish, slowly add 400 g of 10% sodium hydroxide solution to mixture 1, stir continuously during the process, seal with plastic wrap after stirring evenly, place in a 60° C. oven for aging for 25 days, and obtain mixture 2;
[0128] 4. Add 400 g of 5% sulfuric acid solution and 200 g of 10% hydrochloric acid solution to mixture 2, and stir at a stirrer speed of 200 r / min for 60 min for acidification to obtain mixture 3;
[0129] 5. After acidification, filter and dry. After drying, crush the sample and pass it through a 100-mesh sieve. Add 20 g of modified zeolite passed through an 80-mesh sieve and 50 g of bamboo charcoal powder and mix evenly.
[0130] 6. Add 25 g of 75% fluazifop-thiamethoxam water dispersant and 205 g of water glass to the mixture obtained in step 5 and mix and granulate the mixture to a particle size of 4 mm and a length of 7 mm;
[0131] 7. After granulation, place the pellets in an oven at 80°C for drying. After drying, sieve the pellets to remove particles and dust that do not meet the standards, thereby obtaining bentonite cat litter.
[0132] Comparative Example 1
[0133] 1. Crush the clay lithium slag, and pass it through a 100-mesh sieve to obtain a lithium slag raw material;
[0134] 2. Weigh 500g of lithium slag raw material, add 200g of calcium carbonate, and mix thoroughly;
[0135] 3. Place the mixed material in a petri dish, slowly add 300g of 10% sulfuric acid solution and 100g of 10% hydrochloric acid solution to the mixed material, stirring continuously during the process, and after stirring evenly, seal with plastic wrap and place in a 60°C oven for aging for 30 days;
[0136] 4. Add 500 g of 5% sodium hydroxide solution to the aged sample and stir for 60 min at a stirrer speed of 200 r / min for alkalization;
[0137] 5. After acidification, filter and dry. After drying, crush the sample and pass it through a 100-mesh sieve. Add 20 g of modified zeolite passed through an 80-mesh sieve and 50 g of bamboo charcoal powder and mix evenly.
[0138] 6. Add 25 g of 75% fluazifop-thiamethoxam water dispersant and 195 g of water glass to the mixture obtained in step 5 and mix and granulate the mixture to a particle size of 4 mm and a length of 7 mm;
[0139] 7. After granulation, place the pellets in an oven at 80°C for drying. After drying, sieve the pellets to remove particles and dust that do not meet the standards, thereby obtaining bentonite cat litter.
[0140] Comparative Example 2
[0141] 1. Crush the clay lithium slag, and pass it through a 100-mesh sieve to obtain a lithium slag raw material;
[0142] 2. Weigh 500g of lithium slag raw material, add 200g of calcium sulfate, and mix thoroughly;
[0143] 3. Place the mixed material in a petri dish, slowly add 300g of 10% sulfuric acid solution and 100g of 10% hydrochloric acid solution to the mixed material, stirring continuously during the process, and after stirring evenly, seal with plastic wrap and place in a 60°C oven for aging for 30 days;
[0144] 4. Add 500 g of 5% sodium hydroxide solution to the aged sample and stir for 60 min at a stirrer speed of 200 r / min for alkalization;
[0145] 5. After acidification, filter and dry. After drying, crush the sample and pass it through a 100-mesh sieve. Add 20 g of modified zeolite passed through an 80-mesh sieve and 50 g of bamboo charcoal powder and mix evenly.
[0146] 6. Add 25 g of 75% fluazifop-thiamethoxam water dispersant and 195 g of water glass to the mixture obtained in step 5 and mix and granulate the mixture to a particle size of 4 mm and a length of 7 mm;
[0147] 7. After granulation, place the pellets in an oven at 80°C for drying. After drying, sieve the pellets to remove particles and dust that do not meet the standards, thereby obtaining bentonite cat litter.
[0148] Comparative Example 3
[0149] 1. Crush the clay lithium slag, and pass it through a 100-mesh sieve to obtain a lithium slag raw material;
[0150] 2. Weigh 500g of lithium slag raw material, add 150g of calcium carbonate and 100g of calcium sulfate, and mix thoroughly;
[0151] 3. Place the mixed material in a petri dish, slowly add 300g of 10% sulfuric acid solution and 100g of 10% hydrochloric acid solution to the mixed material, stirring continuously during the process, and after stirring evenly, seal with plastic wrap and place in a 60°C oven for aging for 30 days;
[0152] 4. Add 500 g of 5% sodium hydroxide solution to the aged sample and stir for 60 min at a stirrer speed of 200 r / min for alkalization;
[0153] 5. After acidification, filter and dry. After drying, crush the sample and pass it through a 100-mesh sieve. Add 20 g of modified zeolite passed through an 80-mesh sieve and 50 g of bamboo charcoal powder and mix evenly.
[0154] 6. Add 25 g of 75% fluazifop-thiamethoxam water dispersant and 205 g of water glass to the mixture obtained in step 5 and mix and granulate the mixture to a particle size of 4 mm and a length of 7 mm;
[0155] 7. After granulation, place the pellets in an oven at 80°C for drying. After drying, sieve the pellets to remove particles and dust that do not meet the standards, thereby obtaining bentonite cat litter.
[0156] Test Case
[0157] The samples before granulation in the embodiments and comparative examples (the samples obtained in the corresponding step 5) were subjected to component analysis, and the obtained cat litter was subjected to the following performance tests:
[0158] (1) Cat litter water absorption test method: Weigh 300g of cat litter sample and place it in a designated container. Gradually add 0.9% sodium chloride solution, observe its water absorption degree, and measure the water absorption amount.
[0159] (2) Cat litter water absorption time test method: Place a certain amount of cat litter sample in a specified container, pour a certain amount of 0.9% sodium chloride solution into it, and record the time required for the cat litter to completely absorb water.
[0160] (3) Cat litter clumping performance test method: The clumped cat litter sample is freely dropped from a height of 1 meter above the ground. If it does not fall apart when it falls to the ground, it is qualified. The test results are shown in Table 1.
[0161] Table 1
[0162]
[0163] The results show that the method provided by the present invention can convert clay lithium slag into bentonite (i.e., containing montmorillonite, silicon dioxide, aluminum oxide, calcium oxide, calcium oxide, etc.), so that the prepared cat litter has strong and stable water absorption and good agglomeration strength. Wherein "-" in Table 1 indicates that the water absorption time of the cat litter prepared in Comparative Examples 1-3 is too long.
[0164] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0165] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for resource utilization of clay lithium slag, characterized in that: include: Mixing clay lithium slag and calcium salt to obtain a mixture 1; The mixture 1 and the hydroxide are mixed and aged to obtain a mixture 2; The mixture 2 is subjected to an acidification treatment to obtain a mixture 3, and the mixture 3 is used to prepare cat litter.
2. The resource utilization method according to claim 1, characterized in that: The calcium salt includes at least one of calcium carbonate, calcium sulfate, calcium chloride and calcium nitrate; Optionally, the mass ratio of the clay lithium slag to the calcium salt is 1:(0.2-1).
3. The resource utilization method according to claim 1, characterized in that: The hydroxide includes at least one of sodium hydroxide and potassium hydroxide; Optionally, the mass ratio of the mixture 1 to the hydroxide is 1:(0.3-0.6).
4. The resource utilization method according to claim 1, characterized in that: The temperature of the aging treatment is 50°C-80°C; Optionally, the aging treatment time is 15d-45d.
5. The resource utilization method according to claim 1, characterized in that: The acidification treatment comprises contacting the mixture 2 with an acidic compound to obtain the mixture 3; Optionally, the acidic compound includes at least one of sulfuric acid and hydrochloric acid; Optionally, the acidification treatment time is 30min-90min; Optionally, the mass ratio of the clay lithium slag to the acidic compound is 1:(0.8-2).
6. The resource utilization method according to claim 1, characterized in that: Also includes: The mixture 3 is mixed with a deodorant, an antibacterial agent, and a binder, and granulated to obtain a mixture 4, which is used as cat litter; Optionally, the deodorant includes at least one of modified zeolite, bamboo charcoal powder, and coconut shell activated carbon; Optionally, the antimicrobial agent includes at least one of a pyridine aqueous dispersant and a polyguanidine aqueous solution; Optionally, the binder comprises water glass; Optionally, the mass ratio of the clay lithium slag to the deodorant is 1:(0.03-0.15); Optionally, the mass ratio of the clay lithium slag to the antibacterial agent is 1:(0.03-0.06); Optionally, the mass ratio of the clay lithium slag to the binder is 1:(0.30-0.45).
7. The resource utilization method according to claim 6, characterized in that: The particle size of the mixture 4 is 3 mm to 6 mm; Optionally, the length of the mixture 4 is 6 mm-8 mm.
8. The resource utilization method according to any one of claims 1 to 7, characterized in that: Also includes: Drying the mixture 3 for preparing cat litter, or drying the mixture 4 for use as cat litter; Optionally, the drying temperature is 70°C-90°C.
9. The resource utilization method according to claim 1, characterized in that: The particle size of the clay lithium slag is 80-200 meshes.
10. A cat litter, characterized in that: The cat litter is obtained according to the resource utilization method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Lithium slag doped cat litter and preparation thereof
CN118614402A
Cited By
Method for preparing zirconium silicon sodium phosphate nano-powder by taking lithium slag as raw material
CN122212062A